2011
DOI: 10.1080/10934529.2011.535407
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neurobehavioral and biochemical effects in rats exposed to copper smelter dusts

Abstract: Female Wistar rats were instilled per os by gavage with different copper dust samples: P-25 obtained by passing the test material through a 25 μmsieve, and P-0.1 containing soluble matter and ultra-fine, non-soluble<100 nm particulate matter (PM) fraction. The control group received sterile saline. The effects were studied at day 1, 7, and 30 post-exposure, focusing on bronchoalveolar lavage fluid (BALF) analysis (including biochemistry, cell morphology, cell viability, and Clara cell 16 protein concentration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Most studies present in the literature have been performed on human cultured cells (Boczkowski and Hoet, 2010). Very little information at the organism's level is available, except for murine models (Halatek et al, 2011). In the latter, authors showed the deep penetration of copper dust inside the organism, which caused inflammation, Reactive Oxygen Species (ROS) elevation and DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies present in the literature have been performed on human cultured cells (Boczkowski and Hoet, 2010). Very little information at the organism's level is available, except for murine models (Halatek et al, 2011). In the latter, authors showed the deep penetration of copper dust inside the organism, which caused inflammation, Reactive Oxygen Species (ROS) elevation and DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…An association between WMI and/or cerebral palsy with maternal, placental, or fetal infections 32 33 34 with high levels of interleukin (IL)-1, IL-6 in amniotic fluid, and IL-6 in cord blood has been demonstrated 35 . Animal studies using inhalation of dust have shown a decrease in CC16 concentration, impaired anti-inflammatory potential, and resulted in early harmful effects not only to the respiratory tract but also to the nervous system 36 37 . Halatek et al 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies using inhalation of dust have shown a decrease in CC16 concentration, impaired anti-inflammatory potential, and resulted in early harmful effects not only to the respiratory tract but also to the nervous system 36 37 . Halatek et al 37 . found that the CC16 levels of bronchoalveolar lavage fluid in dust-exposed groups were significantly lower than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After uptake it gets distributed within the different cells, detoxification and elimination in the body is maintained by the elegant system which make sure a regular and adequate supply of the micronutrient whereas concurrently avoiding excess levels (4). Copper is a prominent ecotoxicant and human being gets exposed to copper via consumption of water, food and also by inhalation of industrial dust (5)(6). Recent reports suggest that agriculture workers handling of Cu-derived agrochemicals and also Cu-IUDs used by women lead to high plasma levels of copper (7).…”
Section: Introductionmentioning
confidence: 99%